PERAN PEMERINTAHAN DAERAH DALAM PENGEMBANGAN DESA TERTINGGAL DI KECAMATAN RUPAT KABUPATEN BENGKALIS TAHUN 2012 - JUMAIDI HUSIN IRKAMI; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study , entitled The Role of Local Government in Rural Development inSub Rupat Disadvantaged Bengkalis 2012. This research was motivated by Act No. 32of 2004 on regional administration , which in the Act states that the development of theDistrict and City organized with attention to the principles of democracy, communityparticipation, equity and justice as well as attention to the potential diversity regionaldiversity. Law gives full autonomy to the District and the City to establish andimplement policies and initiatives according to the aspirations of its people.Problems contained in this sekripsi is still underdeveloped villages in thedistrict Rupat Bengkalis in 2012. For this study aims to determine how the localgovernment 's role in the development of underdeveloped villages, as well as toovercome the obstacles in the development of underdeveloped villages. Those used inthis research method is a method that describes the qualitative descriptive data. Datacollection techniques used are documentation and field study by interviewing while thedata sources used is primary data obtained from the study sites and is supported bysecondary data.Based on the results of research conducted, Bengkalis government has donesome role to promote development that improves the quality of education, economicinfrastructure development, infrastructure development liaison, communityempowerment and improved quality of plantation society, but not optimal in practice,because there are several factors inhibiting such limited sources of funding, poor qualityof human resources, guidance and supervision is lacking and not well targeted aid that isgiven.Keywords: Roles, Policies, Development, Local Government, Rural Disadvantaged.